Editorial (2007)
“We are talking about new forms of ‘research’, until recently an elite practice — we need professors to back off a little to create communicative space”. “Orlando Fals Borda is one of the great leaders of the participatory action research (PAR) movement in South America. Moreover, he has succeeded in making his work and ideas known in the northern hemisphere. This is no mean feat when ideas have tended to flow from north to south. One of Borda’s great skills has been his ability to network educationalists and intellectuals from the world of education across the boundary that divides the so-called ‘developed world’ from the ‘underdeveloped world’. His work has particularly attracted the attention of university-based educationals trying to reconstruct educational research in a form that places it at the service of hope for greater social justice”.